PEMBELAJARAN BAHASA ARAB MANDIRI MELALUI PLATFORM APLIKASI TIKTOK SEBAGAI TREN BELAJAR MASA KINI - Aminullah, Muhammad Afiq; Al Azmi, Fadilah; Jalal, Darul (STIQ Amuntai, 2022)
technology. Now many internet-based applications have emerged and are popular with the public, including the Tiktok application, which is very popular with local and foreign people. The research is based on the fact that the researcher sees the potential for using the TikTok application to learn Arabic independently. This research is descriptive qualitative research, describing how this TikTok content can be used in independent Arabic learning with tutors who do not know it directly. The research data was taken from content and TikTok accounts that discussed learning Arabic. The results of this study are that in using the Tiktok application, viewers can search for content based on Arabic learning by using hashtags or commonly called hashtags (#). Arabic learning-based content created by content creators varies, namely discussing Arabic vocabulary, Arabic sentences, Arabic rules, etc., with varied approaches and teaching models that are not boring. Based on the data obtained, the researchers considered that the Arabic learning content in the Tiktok application could be used for independent learning models. However, further research is needed to determine the effectiveness of using the Tiktok application in learning Arabic independently.